It can't happen here - Lewis, Sinclair, 1885-1951 (Signet Classics, 2014)
A cautionary tale about the rise of fascism in the United States first published in 1935. During the presidential election of 1936, Doremus Jessup, a newspaper editor, observes with dismay that many of the people he knows support the candidacy of a fascist, Berzelius Windrip. When Windrip wins the election, he forcibly gains control of Congress and the Supreme Court, and, with the aid of his personal paramilitary storm troopers, turns the United States into a totalitarian state. Jessup opposes him, is captured, and escapes to Canada.